An accelerated Rauhut–Currier dimerization enabled the synthesis of (±)-incarvilleatone and anticancer studies - Kotammagari, Tharun K.; Misra, Sweta; Paul, Sayantan; Kunte, Sunita; Gonnade, Rajesh G.; Santra, Manas K.; Bhattacharya, Asish K. (Beilstein Journal of Organic Chemistry, 2023)
The total synthesis of racemic incarvilleatone has been achieved by utilizing unexplored accelerated Rauhut–Currier (RC) dimerization. The other key steps of the synthesis are oxa-Michael and aldol reactions in a tandem sequence. Racemic incarvilleatone was separated by chiral HPLC and the configuration of each enantiomer was determined by single-crystal X-ray analysis. In addition, a one-pot synthesis of (±)-incarviditone has been achieved from rac-rengyolone by using KHMDS as a base. We have also assessed the anticancer activity of all the synthesized compounds in breast cancer cells nonetheless, they exhibited very limited growth suppression activity.
Keywords: dimerization; incarviditone; incarvilleatone; oxa-Michael; Rauhut–Currier

(untitled) - Gao, Y.-P.; Shen, Y.-H.; Zhang, S.-D.; Tian, J.-M.; Zeng, H.-W.; Ye, J.; Li, H.-L.; Shan, L.; Zhang, W.-D. (Org. Lett., 2012)

(untitled) - Chen, Y.-Q.; Shen, Y.-H.; Su, Y.-Q.; Kong, L.-Y.; Zhang, W.-D. (Chem. Biodiversity, 2009)

(untitled) - Brown, P. D.; Willis, A. C.; Sherburn, M. S.; Lawrence, A. L. (Org. Lett., 2012)

(untitled) - Zhao, K.; Cheng, G.-J.; Yang, H.; Shang, H.; Zhang, X.; Wu, Y.-D.; Tang, Y. (Org. Lett., 2012)

U.S. Patent - Rauhut, M. M.; Currier, H. (Preparation of dialkyl 2-methyleneglutarates, 1963)

(untitled) - Jeon, S.; Han, S. (J. Am. Chem. Soc., 2017)

(untitled) - Aroyan, C. E.; Dermenci, A.; Miller, S. J. (Tetrahedron, 2009)

(untitled) - Dermenci, A.; Selig, P. S.; Domaoal, R. A.; Spasov, K. A.; Anderson, K. S.; Miller, S. J. (Chem. Sci., 2011)

(untitled) - Marqués-López, E.; Herrera, R. P.; Marks, T.; Jacobs, W. C.; Christmann, M. (Synthesis, 2013)

(untitled) - Kotammagari, T. K.; Gonnade, R. G.; Bhattacharya, A. K. (Org. Lett., 2017)

(untitled) - Dumez, E.; Rodriguez, J.; Dulcère, J.-P. (Chem. Commun., 1997)

(untitled) - Enders, D.; Haertwig, A.; Raabe, G.; Runsink, J. (Eur. J. Org. Chem., 1998)

(untitled) - Lesch, B.; Brase, S. (Angew. Chem., Int. Ed., 2004)

(untitled) - Nising, C. F.; Ohnemüller (née Schmid), U. K.; Bräse, S. (Angew. Chem., Int. Ed., 2006)

(untitled) - Xiong, X.; Ovens, C.; Pilling, A. W.; Ward, J. W.; Dixon, D. J. (Org. Lett., 2008)

(untitled) - Jeon, S.; Park, J.; Han, S. (Synlett, 2017)

(untitled) - Valkute, T. R.; Aratikatla, E. K.; Gupta, N. A.; Ganga, S.; Santra, M. K.; Bhattacharya, A. K. (RSC Adv., 2018)

(untitled) - Kotammagari, T. K.; Paul, S.; Barik, G. K.; Santra, M. K.; Bhattacharya, A. K. (Org. Biomol. Chem., 2020)

(untitled) - Cole, S. P. C. (Cancer Chemother. Pharmacol., 1986)